Designing for Success: Evaluating Immersive Virtual Reality Learning in Nursing Education From a Remote Context - Harder, Nicole; Graveline, Kellie; Turner, Sufia; Mudashiru, Temilolu; Workum, Kim (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
Purpose: This study aimed to explore how undergraduate nursing students in rural programs experience immersive virtual reality (IVR) as a strategy to support clinical learning and professional development. Situated learning theory (Lave & Wenger, 1991) provided the theoretical framework for this study.Method: This qualitative study used focus groups and interviews with nursing students from two rural campuses of a Canadian undergraduate nursing program. Data were analyzed thematically, informed by situated learning theory.Results: Participants identified four key influences on their learning with IVR: orientation and readiness to engage, physical and technological context, faculty facilitation, and realism of the simulation. IVR offered opportunities to engage in complex clinical decision-making and promoted confidence and active participation.Conclusion: IVR, when integrated into nursing curricula using principles of situated learning theory, may support learner engagement and confidence among students in rural programs. Findings suggest the importance of thoughtful design, facilitation, and contextual relevance in virtual simulation experiences.